A mega health camp at a rural municipality of Eastern Nepal: a cross-sectional study revealing the state of health among the population served - Neupane, Durga; Jaiswal, Lokesh S.; Upadhaya, Sandesh R.; Pokhrel, Nabin; Acharya, Anil; Tiwari, Apil; Aryal, Yadav; Pokharel, Paras K. (International Journal Of Community Medicine And Public Health, 2021)
Background: Health camps are usually targeted to underprivileged people of rural places. They help in the awareness, preventive and curative services to those people. A mega health camp was conducted in Yangwarak rural municipality of Panchthar district of Eastern Nepal. All the services including medicines, consultation charges, laboratory services and imaging were free of cost. Methods: It’s a prospective cross-sectional study comprised of all consecutive patients attending the camp in Yangwarak rural municipality of Panchthar district in Eastern Nepal. All the patients attending the free camp were taken as a case. Necessary information was deducted and enrolled in this study. The data was entered into the Microsoft excel software and analysed using statistical package for social studies (SPSS) software 23.0 version. Results: A total of 1656 people were directly benefitted with consultation of a dozen of department. 58.7% were female and rest were male. Majority of people had gastrointestinal issues. The knowledge, attitude and practice to health was poor. Conclusions: Keeping in mind the findings of the camp, this only represents the tip of iceberg. There are many such places with needy people who need the help of health professionals and proper address by the government. The preventive approach to health should be magnified even more.